2017
DOI: 10.1016/j.biortech.2016.12.114
|View full text |Cite
|
Sign up to set email alerts
|

Novel bio-electro-Fenton technology for azo dye wastewater treatment using microbial reverse-electrodialysis electrolysis cell

Abstract: Development of sustainable technologies for treatment of azo dyes containing wastewaters has long been of great interest. In this study, we proposed an innovative concept of using microbial reverse-electrodialysis electrolysis cell (MREC) based Fenton process to treat azo dye wastewater. In such MREC-Fenton integrated process, the production of HO which is the key reactant of fenton-reaction was driven by the electrons harvested from the exoelectrogens and salinity-gradient between sea water and fresh water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 42 publications
5
72
0
Order By: Relevance
“…The domestic wastewater was collected from primary clarifier (Lyngby Wastewater Treatment Plant, Copenhagen, Denmark) which was amended by 1 g/L acetate prior to use. The characteristics of the wastewater were described previously [10]. After enrichment for around one month, mature anodic biofilm was formed when stable maximum voltage (~650 mV) was observed in several successive batches.…”
Section: Reactor Setup and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The domestic wastewater was collected from primary clarifier (Lyngby Wastewater Treatment Plant, Copenhagen, Denmark) which was amended by 1 g/L acetate prior to use. The characteristics of the wastewater were described previously [10]. After enrichment for around one month, mature anodic biofilm was formed when stable maximum voltage (~650 mV) was observed in several successive batches.…”
Section: Reactor Setup and Operationmentioning
confidence: 99%
“…Latterly, it was found that the treatment capacity can be boosted by supplying small amounts of electricity (0.2-1.0 V) to the system, due to the improved H 2 O 2 production [19]. In lights of the advantages in H 2 O 2 production and utilization, the bio-electro-Fenton systems have been applied to treat a broad spectrum of recalcitrant organic pollutants, including azo days, aniline, pharmaceuticals, p-nitrophenol and so on [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fenton's reagent is a precursor of hydroxyl free radicals; these madly reactive hydroxyl free radicals attack dye substrate molecules at the sites of multiple bonds and carry out either excessive hydroxylation of dye contaminants or causes dehydrogenation of dye molecules, hence producing stable inorganic materials directly or indirectly converting the dye pollutant into biodegradable and safe materials. Fenton's processes offer a remarkable efficiency and can be extended to much broader spectrum of dyes due to its fabulous non-selectivity [22]. Recently photo-Fenton's process, i.e.…”
Section: Advanced Oxidation Processes (Aops)mentioning
confidence: 99%
“…That is why environmental chemists were chewing their nails to explore more advanced, effective and non-selective techniques to achieve dye abatement goals. Thanks to electrochemical techniques which have taken the bull of organic pollutants by horns and have controlled the aquatic pollution to a great extent [22].…”
Section: Microbiological and Enzymatic Degradation Techniquesmentioning
confidence: 99%
“…MPD and its derivatives in wastewater are very numerous and miscellaneous, exerting a negative effect on wastewater treatment. When investigating such wastewater, the methods used by various researchers can be summed up as physical separation methods, chemical oxidation methods, and biological treatment . Compared to high‐cost chemical oxidation and time‐consuming biological treatment, physical separation stands out in the treatment of dye wastewater.…”
Section: Introductionmentioning
confidence: 99%